Question
upstudy study bank question image url

olve \( \sqrt{x+5}+1=\frac{6}{\sqrt{x+5}} \)

Ask by Boyd Alexander. in Nigeria
Feb 15,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x = -1 \)

Solution

Solve the equation \( \sqrt{x+5}+1=\frac{6}{\sqrt{x+5}} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\sqrt{x+5}+1=\frac{6}{\sqrt{x+5}}\) - step1: Find the domain: \(\sqrt{x+5}+1=\frac{6}{\sqrt{x+5}},x>-5\) - step2: Multiply both sides of the equation by LCD: \(\left(\sqrt{x+5}+1\right)\sqrt{x+5}=\frac{6}{\sqrt{x+5}}\times \sqrt{x+5}\) - step3: Simplify the equation: \(x+5+\sqrt{x+5}=6\) - step4: Move the constant to the right side: \(x+\sqrt{x+5}=6-5\) - step5: Calculate: \(x+\sqrt{x+5}=1\) - step6: Move the variable to the right-hand side: \(\sqrt{x+5}=1-x\) - step7: Evaluate: \(\sqrt{x+5}=1-x,1-x\geq 0\) - step8: Evaluate: \(\sqrt{x+5}=1-x,x\leq 1\) - step9: Solve the equation: \(\begin{align}&x=4\\&x=-1\end{align},x\leq 1\) - step10: Find the intersection: \(x=-1\) - step11: Check if the solution is in the defined range: \(x=-1,x>-5\) - step12: Find the intersection: \(x=-1\) - step13: Check the solution: \(x=-1\) The solution to the equation \( \sqrt{x+5}+1=\frac{6}{\sqrt{x+5}} \) is \( x=-1 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the equation \( \sqrt{x+5} + 1 = \frac{6}{\sqrt{x+5}} \), we'll start by making a substitution. Let \( y = \sqrt{x+5} \). Then the equation becomes: \[ y + 1 = \frac{6}{y} \] Next, we can eliminate the fraction by multiplying both sides by \( y \) (assuming \( y \neq 0 \)): \[ y^2 + y = 6 \] Rearranging this gives us a quadratic equation: \[ y^2 + y - 6 = 0 \] Now, we can factor this equation: \[ (y - 2)(y + 3) = 0 \] Setting each factor to zero gives us: \[ y - 2 = 0 \quad \text{or} \quad y + 3 = 0 \] So, we have: \[ y = 2 \quad \text{or} \quad y = -3 \] Since \( y = \sqrt{x+5} \) must be non-negative, we discard \( y = -3 \). Thus, we have: \[ y = 2 \] Now, substituting back to find \( x \): \[ \sqrt{x+5} = 2 \] Squaring both sides: \[ x + 5 = 4 \] Solving for \( x \): \[ x = 4 - 5 = -1 \] Finally, we should check our solution by substituting \( x = -1 \) back into the original equation: \[ \sqrt{-1 + 5} + 1 = \frac{6}{\sqrt{-1 + 5}} \] Calculating this gives: \[ \sqrt{4} + 1 = \frac{6}{\sqrt{4}} \] This simplifies to: \[ 2 + 1 = \frac{6}{2} \] Which results in: \[ 3 = 3 \] This confirms our solution works. Therefore, the solution to the equation \( \sqrt{x+5}+1=\frac{6}{\sqrt{x+5}} \) is: \[ \boxed{-1} \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy